Antimicrobial Activity of the Extract and Fraction of Red Betel Leaf (Piper betle Linn.) - Julia Reveny (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2011)
Antimicrobial activity of ethanolic extract of red betel leaf (Piper betle Linn.), n-hexane fraction and ethyl acetate against Staphylococcus aureus, Escherichia coli and Candida albicans had been carried out. Red betel leaf powder was extracted with 80% ethanol, followed fractionate with n-hexane and ethylacetate. The result was tested in vitro with agar diffusion method using a steel cylinder. Phytochemical screening test was performed to betel leaf powder, while the extract and each fraction were tested with antimicrobial activity in vitro. The thin layer chromatography (TLC) was performed with stationary phase silica gel GF 254 and moving phase of n-hexane: ethyl acetate (8:2), (7:3), (6:4), (5:5) toluene: ethyl acetate (6:4), chloroform: methanol (7:3). Phytochemical screening result indicated the presence of glycosides, triterpenoids/steroids, flavonoids, tannins and anthraquinon. Both of 80% ethanol extract and fractions of red betel leaf (Piper betle Linn.) have antimicrobial activity with Minimum Inhibitory Concentration (MIC) of ethanol extract 80% against Staphylococcus aureus, Escherichia coli and Candida albicans are 2.5%, 2.5%, 10%. The n-hexane fractions were 20%, 15%, 10% and the ethyl acetate fractions are 2.5%, 1%, 2.5%, while the water fraction did not show any antimicrobial effects. The ethanol extract indicated a higher inhibitory effect in Escherichia coli, while the ethyl acetate fraction showed a higher effect on Staphylococcus aureus and Candida albicans. The TLC results showed the presence of terpenoids/steroids, flavonoids, and tannins in ethanol extract, tannin and flavonoid in ethyl acetate, terpenoid/steroids in n-hexane fraction.